The impact of radiation therapy on vaginal biomechanical properties. (September 2021) - Matanes, Emad; Linder, Revital; Lauterbach, Roy; Mick, Ido; Matanis, Jawad; Abdah-Bortnyak, Roxolyana; Reiss, Ari; Amit, Amnon; Lowenstein, Lior
Abstract: Objective: In women with cervical cancer (CC), treatment with radiation causes changes in vaginal biomechanical properties, anatomy and function. The aims of the current study were to objectively assess effects of radiotherapy (RT) on vaginal elasticity, wall mobility and contraction strength; and to evaluate associations of these changes with sexual function. Study design: This prospective cohort study was approved by our Institutional Review Board. Between May 2018 and June 2020, women with CC who were candidates for RT were eligible to participate. Participants underwent vaginal tactile imaging (VTI) evaluation and were asked to fill the Female Sexual Function Index (FSFI) questionnaire at the time of first RT session and at a 6-month post-treatment follow up visit. Women who underwent radical hysterectomy, or had pelvic side-wall, pelvic or distant organ metastasis were not included. Results: A total of 25 women with locally advanced CC were included in the final analysis. The mean age was 39 ± 2.7 years, the mean BMI was 24.8 ± 2.2 kg/m 2 and the median parity was 2 (range: 1–5). Following RT, the mean scores for vaginal elasticity and vaginal tightening were significantly lower than at pre-treatment: 11.3 ± 2.5 vs. 28.3 ± 9, P < 0.0001 and 2.6 ± 0.7 vs. 16.7 ± 3, P < 0.0001, respectively. Following RT, significant decreases were demonstrated in vaginal wall mobility and pelvic muscle contraction strength: from 1.77 ± 0.34 to 0.36 ± 0.15, P < 0.0001 and from 2.55 ± 0.48 to 0.52 ± 0.23, P < 0.0001, respectively. Compared to pre-treatment, post-RT vaginal length was significantly shorter (3.30 ± 0.22 vs. 7.64 ± 0.63, P = 0.0023) and sexual intercourse frequency significantly lower: 1 (range 1–2) vs. 2 (range 1–4), P = 0.014). The mean total FSFI score was significantly lower following RT (6.7 ± 1 vs. 14.5 ± 2.7, P < 0.0001). Conclusions: Women with locally advanced CC who have been treated with RT exhibit persistent vaginal biomechanical changes that compromise sexual activity and result in considerable distress.